1986
DOI: 10.1007/bf02535638
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding fish oils, vegetable oils and clofibrate on the ketogenesis from long chain fatty acids in hepatocytes

Abstract: Groups of rats were fed diets containing 25% fish oil (FO), 25% soybean oil, 25% partially hydrogenated fish oil (PHFO), 25% partially hydrogenated soybean oil (PHSO), 25% partially hydrogenated coconut oil or 0.3% clofibrate for 3 wk. After the animals were fasted for 24 hr, hepatocytes were isolated and ketogenesis from added palmitate, linoleate cis and trans, arachidonate and docosahexaenoate was measured. Ketogenesis after oil feeding was significantly stimulated (two- to threefold) only in cells from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Significantly, potentially ketogenic polyunsaturated fatty acids (PUFAs) such as linoleic, arachidonic and docosahexaenoic acids [15] exhibit facile transfer across the blood-brain barrier during the suckling period [16,17]. Furthermore recent hybridization studies in situ [18,19] have demonstrated the localization of the peroxisome proliferator-activated receptor α (PPARα), a nuclear transcription factor that is activated by a variety of PUFA ligands [20,21], to certain brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, potentially ketogenic polyunsaturated fatty acids (PUFAs) such as linoleic, arachidonic and docosahexaenoic acids [15] exhibit facile transfer across the blood-brain barrier during the suckling period [16,17]. Furthermore recent hybridization studies in situ [18,19] have demonstrated the localization of the peroxisome proliferator-activated receptor α (PPARα), a nuclear transcription factor that is activated by a variety of PUFA ligands [20,21], to certain brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…EPA and DHA have been suggested to be poor substrates for the diacylglycerol acyltransferase, hence diminishing the flux of these fatty acids into triacylglycerols [7][8][9] and conversely favouring that into phospholipids. High fat diets have been shown to increase rates of mitochondrial β-oxidation [10] using rat liver mitochondria or isolated rat hepatocytes, in particular with diets containing partially hydrogenated oil [11]. Dietary supplementation with EPA or DHA has, with isolated rat hepatocytes, also been demonstrated to increase cellular β-oxidation [12].…”
Section: Introductionmentioning
confidence: 99%
“…[23] have reported that dietary fish oil accelerates hepatic ketogenesis. Similar results were also found by Wong et al [24] reporting diminished lipogenesis and increased fatty acid oxidation in perfused livers of fish oil fed rats compared with rats receiving safflower oil.…”
Section: Discussionmentioning
confidence: 98%